The magmatic system beneath Torfajökull volcano, Iceland, throughradar and seismic interferometric analysis - Martins, Joana E. (author); Hooper, Andy (author); Ruigrok, E.N. (author); Draganov, D.S. (author); Hanssen, R.F. (author); White, Robert (author); Soosalu, Heidi (author) (2014)
Torfajökull is the largest silicic volcanic centre in Iceland lying at the intersection of the rift zone (MidAtlantic Ridge) and the transform zone that connects to Reykjanes peninsula. It erupts infrequently,with only two eruptions in the last 1200 years, the latest of which was over 5 centuries ago. Yet, itsactive tectonic setting, persistent high and low frequency seismicity, deformation and geothermalactivity within its large caldera (18x12 km diameter) indicate the continued presence of a long-lasting magma chamber. Here we speculate on possible geometry, size and depth of the Torfajökullmagma chamber by using radar interferometry (InSAR) and seismic interferometry (SI).Using InSAR time series analysis we detect a surface subsidence pattern at rates of up to ~13 mm yr-1in the SW region of Torfajökull ́s caldera, on-going since at least 1993. The subsidence rate isconstant in time, and perhaps due to a cooling magma chamber. The data can be fit reasonably wellusing a model of a NE-SW oriented spheroidal body at ~5 km depth. As the deflating area correlatesspatially with the area of geothermal activity, deflation may also be the surface response due to anactive hydrothermal circulation.To gain more insight into the geometry of Torfajökull’s magmatic system and rock properties of thesubsurface, we apply ambient noise seismic interferometry (SI) by cross-correlation of ambient noise.With this technique we can detect velocity variations, which can correspond to the edges of dikes ormolten magma bodies. Our tomographic results give reliable results of velocity variations within adepth range of 2 km to 7.5 km. We find high velocity zones that we interpret as old dike intrusions.Low velocity anomalies (>5%), which usually indicate the presence of warmer material, are locatedon the southeast and southwest part of the volcano, outside the volcano caldera.Finally we compare both InSAR and SI results. The hypothesis of a magma chamber under thesubsidence area detected by InSAR does not seem to fit the tomographic ...